Lunan a history of the Filipino built environments - National Commission for Culture and the Arts.; Turalba Foundations, Inc. (Manila NCCA, 2012)
The three-part video Lunan alludes to the condition on which environment is built as well as the process of making it ; the design of the interior, the planning of the city, and the cultivation of landscape. In this exploration of space in the Philippine context, the project foregrounds the environment or nature, as well as the agency of the people inhabiting to shape it, to built it, to engage in the myriad schemes of culture.
Episode 1: Loob: interior design in the Philippines / written by Raquel Florendo, narrated by Elizabeth Enriquez (30 mins. and 27 secs) -- Episode 2: Lungsod: urban design in the Philippines / written by Maria Cristina Valera Turalba, narrated by Maureen Anne Araneta (38 mins and 51 secs) -- Episode 3: Luntiang lupain: landscape architecture in the Philippines / written by Ildefonso P. Santos, Jr. and Gerard Lico, narrated by Apollo Abraham ( 38 mins and 36 secs)
Produced and directed by Gerard Lico, original score by Leujim Martinez, Bryan Oscar Ong [and] Dino Miguel Villarica associate producers, Thomas Roel Baquilod production manager, Maria Cristina V. Turalba executive producer.
Keywords: Architecture -- Philippines; Landscape architecture -- Philippines; Urban planning -- Philippines; Interior design -- Philippines